Global burden and trends of viral hepatitis among women of childbearing age from 1990 to 2021 - Yang, Shaojie; Zhong, Lin; Huang, Lu; Lin, Shengyuan; Li, Yubin (Frontiers in Microbiology, 2025)
BackgroundThe burden and trends of viral hepatitis in women of childbearing age (WCBA) are rarely quantified. This study aimed to assess the global, regional, and national incidence and prevalence rates among WCBA from 1990 to 2021.MethodsFrom 1990 to 2021, we retrieved data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 on the incidence and prevalence of hepatitis A, B, C, and E for WCBA. Estimated annual percent change in the age-standardized incidence and prevalence rates were calculated to quantify the temporal trend.ResultsIn 2021, it was estimated that there were 42,266,708 new cases and 109,107,759 prevalent cases of viral hepatitis among WCBA globally. AHA had the highest incidence rate, while CHB had the highest prevalence rate globally. Notably, AHA and AHE were emerging in low-endemic regions. Generally, the burden of viral hepatitis decreased with higher SDI levels, except for AHA. Between 1990 and 2021, the global age-standardized incidence rate for viral hepatitis among WCBA decreased annually by −1.11% for acute hepatitis A (AHA), −1.24% for AHB, and −0.18% for AHC, −0.34% for AHE, with more significant reductions observed for chronic hepatitis B (CHB) and CHC at −1.33% and −0.29%, respectively. Furthermore, the burden of viral hepatitis continued to rise in lower-SDI regions, and the proportion of younger individuals affected increased as SDI decreased.ConclusionsAlthough the incidence and prevalence rates of viral hepatitis have decreased in recent decades, notable regional and demographic disparities remain. These concerning trends are especially pronounced in low-SDI regions, making it essential to tackle the disparities in healthcare resource allocation for WCBA across areas with varying SDI levels.